Cosmic Explosions in Three Dimensions 2004
DOI: 10.1017/cbo9780511536236.003
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric observations of supernovae

Abstract: Abstract.We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This group of supernovae includes also SN 1991T, SN 1997br (Li et al 1999), and SN 2000cx (Li et al 2001, not in our sample but well observed. However, it should be noted that the spectroscopically SN 1991T-like event -SN 1995ac (Filippenko & Leonard 1995) does not show the bump that defines this group.…”
Section: The Shapes Of the Color-magnitude Diagrams Of Type Ia Supern...mentioning
confidence: 84%
“…This group of supernovae includes also SN 1991T, SN 1997br (Li et al 1999), and SN 2000cx (Li et al 2001, not in our sample but well observed. However, it should be noted that the spectroscopically SN 1991T-like event -SN 1995ac (Filippenko & Leonard 1995) does not show the bump that defines this group.…”
Section: The Shapes Of the Color-magnitude Diagrams Of Type Ia Supern...mentioning
confidence: 84%
“…Type Ic supernovae (SNe) are H-/He-poor core-collapse supernovae Clocchiatti & Wheeler (1997); Filippenko (1997); Matheson et al (2001); Modjaz et al (2016). Significant diversity can be found among the He-poor SNe whose data have been published (Bianco et al 2014;Taddia et al 2015;Lyman et al 2016;Prentice et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to continuum polarization, which points to global asymmetries, line polarization features can provide specific clues to the nature of SN ejecta and their surrounding circumstellar material (CSM; Leonard et al 2000aKawabata et al 2002;Kasen et al 2003;Wang et al 2003aWang et al , 2003bWang et al ,. 2004Filippenko & Leonard 2004;Chornock et al 2006;.…”
Section: Introductionmentioning
confidence: 99%